Liver kinase B1 expression is associated with improved prognosis and tumor immune microenvironment features in small cell lung cancer - Dal Maso, Alessandro; Ferrarini, Federica; Esposito, Giovanni; Minuzzo, Sonia Anna; Puggia, Anna Maria; Pezzuto, Federica; Zulato, Elisabetta; Bao, Loc Carlo; De Nuzzo, Mattia; Ferro, Alessandra; Frega, Stefano; Pasello, Giulia; et al. (Frontiers in Oncology, 2025)
BackgroundSmall cell lung cancer (SCLC) is characterized by early metastatic potential and poor prognosis. Liver kinase B1 (LKB1) is a tumor suppressor and a cell metabolism regulator. LKB1 downregulation has been associated with a cold tumor immune microenvironment (TIME). We aimed to analyze the role of LKB1 in SCLC in relation to its association with overall survival (OS) and TIME components.MethodsWe retrospectively evaluated SCLC patients consecutively treated at our institution from 1996 to 2020 with available tissue. LKB1, PD-L1 on tumor cells and on tumor immune-infiltrating cells, CD8, and FOXP3 were evaluated by immunohistochemistry (IHC), categorized according to predefined cutoffs. The primary endpoint was the description of LKB1 expression, and the secondary endpoints were the association with prognosis and TIME features.ResultsTissue samples of 138 out of 481 SCLCs were adequate for molecular analyses. Eighty patients had limited stage (LS) at diagnosis and 58 had extended stage (ES). The median LKB1 IHC score was 4. Patients with IHC score >4 (n = 67) were classified as LKB1-positive. The probability of LKB1 positivity was higher in LS [odds ratio 2.78, 95% confidence interval (95% CI) 1.18–7.14]. At the data cutoff (2 January 2024), 123 patients died. The median OS (mOS) was 14.0 months (95% CI 11.5–19.4). mOS was significantly longer in patients with LKB1-positive expression [32.4 months (95% CI 13.6–62.4) vs. 11.2 months (95% CI 8.7–14.7); p < 0.001]. At multivariate analysis, positive LKB1 expression, LS, and no weight loss at diagnosis were confirmed as independent positive prognostic factors. TIME features were evaluated in 70 patients. Unexpectedly, LKB1-negative samples were more likely to show CD8+ tumor-infiltrating lymphocytes (TILs; p = 0.013). No association with PD-L1 expression nor the presence of FOXP3+ TILs was found.ConclusionLKB1 expression is a potential positive prognostic marker in SCLC. In this series, LKB1 expression was negatively associated with the presence of CD8+ TILs.